Different stimulation protocols for oocyte cryropreservation in oncological patients: a retrospective analysis of single university centre. (2nd December 2015) - Simi, Giovanna; Obino, Maria Elena Rosa; Casarosa, Elena; Litta, Pietro; Artini, Paolo Giovanni; Cela, Vito
Abstract: Objective : To analyze the results obtain in cancer patients who receive the same controlled ovarian stimulation protocol, started in two different moments of the menstrual cycle, follicular or luteal phase. The stimulation is performed before cancer treatment in order to preserve fertility through oocytes cryopreservation. Study design : The study is a retrospective analysis about 25 cancer patients at our centre, Department of Reproductive Medicine of University of Pisa, in order to preserve their fertility before cancer treatment. Patients are divided into two groups depending on the menstrual cycle phase, follicular or luteal phase, at the moment of first examination. Standard stimulation protocol with gonadotropins is administered in the follicular group, whereas in the second group we use GnRH (gonadotropin-releasing hormone) antagonist before gonadotropins administration in order to have a rapid luteolysis. The outcome measures are the number of days needed before starting procedure, duration of stimulation, cumulative dosage of gonadotropins number of oocyte retrieved and percentage of mature oocytes. Results : Any difference showed between two groups based on days of stimulation, total amount of gonadotropins administered and the number of good mature quality oocytes was retrieved. The real difference is the number of days needed to start the procedure, lesser in the luteal group. Conclusions : This study suggests that oocytes can be obtained before cancer treatment, irrespective of menstrual cycle phase without compromising the efficacy of procedure. Moreover, starting ovarian stimulation anytime during menstrual cycle allows the patients to not postpone the beginning of cancer treatment. Different stimulation protocols, according to different kinds of disease, are available in order to obtain the maximum results without any complication for patients.